Small Intestine Protection of Mica Against Non-Steroidal Anti-Inflammatory Drugs-Injury Through ERK1/2 Signal Pathway in Rats - Shuo Zhang; Yinghua He; Zheng Shi; Jianping Jiang; Beihui He; Sumei Xu; Zhengyu Fang (Frontiers Media S.A., 2019)
Objective: The impact of non-steroidal anti-inflammatory drugs (NSAIDs) to damage the small intestine has been well known. Mica, one kind of natural clay, has been widely marketed in China for the treatment of gastric diseases. However, the role and mechanism of mica in small intestinal injure is still unknown. The study was designed to declare the effects of mica on intestinal injury induced by diclofenac in rats.Methods: Rats were randomly divided into control, model, PAR-2 agonist group (SLIGRL-NH2group), control peptide group (LRGILS-NH2 group), and ERK blocker group (eight mice per group). Morphological changes of mucous membrane of small intestine were observed, and the expression of tryptase, PAR-2, and p-ERK1/2 was measured by immunohistochemistry and western blot. PAR-2 mRNA was tested by qRT-PCR. Rats were also randomly divided into control, model, and mica group (eight mice per group). Morphological changes of mucous membrane were observed. The expression of tryptase, PAR-2, and p-ERK1/2 was measured by immunohistochemistry.Results: The expression of trypsin, PAR-2, and p-ERK1/2 was increased in model group compared with control. The expression of PAR-2 and p-ERK1/2 was increased in SLIGRL-NH2 group compared with model, but not LRGILS-NH2 group. The expression of PAR-2 was down-regulated in ERK blocker group compared with SLIGRL-NH2 group. Macroscopically visible lesions of mucous membrane were positively correlated with the expression of PAR-2 and p-ERK1/2. Furthermore, we also found that mica could inhibit small intestinal injure, as evidenced by the improvement of macroscopic damage. Tryptase, PAR-2, and p-ERK1/2 expression was down-regulated in mica group compared with model group.Conclusion: Mica inhibit small intestinal injury induced by NSAIDs via ERK signaling pathway.